The utilisation of nutrient elements in soilless cultures of vegetable production - Rácz, I-né; Takácsné Hájos, M. (International Journal of Horticultural Science, 2007)
Vegetable production in greenhouses may impair the ecological balance of the environment substantially as far as being uncontrolled. Soilless cultures especially should be handled thoughtfully. A fraction of the nutrients administered, more than 25-30%, is doomed to be lost in an open system, and the resulting ecological risk is accompanied with increasing costs of the production. Experiments have been conducted with the purpose of estimate the amount of nutrients involved. According to the results, as a mean, 30-80 per cent of the main nutrients was utilised. The rate of nutrient utilisation is influenced by the plant species involved as well as by the circumstances of production. One of its most important components is the irrigation, which determines the amount of overflow and of its salt content.